Application Of DDM To Some Rock Pressure Problems In Japanese Deep Coal Mines - Yoshiaki Fujii (International Conference on Ground Control in Mining, 1992)
Displacement Discontinuity Method (DDM), which was originally developed by Crouch,S.L., is a powerful tool to calculate mechanical disturbances due to tabular excavations. Three topics on DDM applications to strata control problems in Japanese deep coal mines are described. First, is numerical simulation of microseismicity induced by longwall mining in Horonai Coal Mine. Microseismicity in the mine had been monitored by a mine-wide seismic array. Location of microseismic events and intensity of seismicity were well simulated. In the simulation procedure based on DDM, first, zones where a failure condition is satisfied by the advance of mining are detected. Then, the seismic moments, which indicate the intensity of seismicity, at the failure zones are evaluated. Second, is prediction of the shaft damage due to mining in Sumitomo Akabira Colliery. In this mine, the limit angle of the shaft pillar was changed from 600 to 800 to increase the amount of minable coal volume without increasing mining depth. Displacement of the shaft axis has been measured to assess the damage due to mining around the shaft pillar. In the calculation based on DDM, a fault intersecting the shaft and the ground surface are considered. Observed and predicted displacement of the shaft axis agreed well. Third, is the roadway deformation in Taiheiyo Coal Mine. Attainable maximum stress for a roadway was calculated considering three faults intersecting the roadway. It was realized that the roadway's convergence is related to the calculated stress by simple equations.